2007
DOI: 10.1097/cji.0b013e31814fb2ec
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemotherapy With Gemcitabine Plus 5-fluorouracil and Chemoimmunotherapy in Metastatic Renal Cell Cancer (mRCC)

Abstract: Several phase II trials have shown that gemcitabine and fluoropyrimidines have marginal but definite activity in patients with metastatic renal cell cancer (mRCC). We retrospectively analyzed the 193 mRCC patients consecutively seen in our institutions during the last 11 years, of whom 39 were treated with chemotherapy (CT): 16 were treated with CT alone (gemcitabine and 5-fluorouracil) and 23 with the same regimen plus low dose of interleukin-2 and interferon-alpha. The main end point of the analysis was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…5,6 The few published trials showed at the best an RR of <10% to 15%, with the combination of gemcitabine and 5-fluorouracil representing the best regimen. [15][16][17] In an earlier analysis of a series of mRCC patients treated with the combination of CT (gemcitabine+5-fluorouracil)+IT (low doses of IL-2+IFN-a), we described a modest but definite activity of this combination with a good disease-control rate and tolerability. 15…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The few published trials showed at the best an RR of <10% to 15%, with the combination of gemcitabine and 5-fluorouracil representing the best regimen. [15][16][17] In an earlier analysis of a series of mRCC patients treated with the combination of CT (gemcitabine+5-fluorouracil)+IT (low doses of IL-2+IFN-a), we described a modest but definite activity of this combination with a good disease-control rate and tolerability. 15…”
mentioning
confidence: 99%
“…5,6 The few published trials showed at the best an RR of <10% to 15%, with the combination of gemcitabine and 5-fluorouracil representing the best regimen. [15][16][17] In an earlier analysis of a series of mRCC patients treated with the combination of CT (gemcitabine+5-fluorouracil)+IT (low doses of IL-2+IFN-a), we described a modest but definite activity of this combination with a good disease-control rate and tolerability. 15 The rationale for combining CT with anti-vascular endothelial growth factor (VEGF) drugs is based not only on preclinical data showing that anti-VEGF therapy normalizes tumor vascularization and improves the distribution of CT agents to tumoral cells, 18 but also on the results of clinical trials in other tumors 19 ; bevacizumab was the first antiangiogenic agent studied in a randomized double-blind phase II trial for the treatment of mRCC.…”
mentioning
confidence: 99%
“…A good activity of chemotherapy has been described by our group in patients with mRCC progressing to a regimen of low doses of IL-2+IFN-α [3]. Several studies also showed activity of chemotherapy alone or in combination with target therapy.…”
Section: Discussionmentioning
confidence: 89%
“…CT was rarely used against mRCC, and it was employed only for progressing, unresponsive patients [1,2]. The few published trial showed at the best a response rate (RR) of 10-15 %, with the combination of gemcitabine and 5-fluorouracil representing the best regimen [3,4]. In a previous analysis of a series of mRCC patients treated with the combination of chemotherapy (gemcitabine+5-fluorouracil) plus IT (low doses IL-2+IFN-α), we described a modest but definite activity of this combination with a good disease control rate and tolerability [3].…”
Section: Introductionmentioning
confidence: 98%
“…A recent study showed gemcitabine with 5-fluorouracil was able to stabilize disease in approximately 25.6% of metastatic renal cell patients. 12 Overall our patient's palliative chemotherapy and immunotherapy regimen did delay his initial skeletal event and subsequently postponed the development of his olecranon metastasis.…”
Section: Discussionmentioning
confidence: 95%